KANDUNGAN DAN KOMPOSISI PIGMEN Sargassum sp. PADA PERAIRAN TELUK AWUR, JEPARA DENGAN PERLAKUAN SEGAR DAN KERING - Dian Resita; Windu Merdekawati; AB Susanto; Leenawaty Limantara (Universitas Gadjah Mada, 2010)
Sargassum sp. is one of seaweed species that abundance and widespread in Indonesia. Besides alginates, Sargassum sp. also contains photosynthesis pigment i.e. chlorophyll a and c, carotene, and fucoxanthin. To date, Sargassum sp. is only used in the form of alginates colloid for industrial raw material with drying process prior to production. Dried process of Sargassum sp. cause pigment degradation especially chlorophyll. The aim of this research was to determine the content and pigment composition of fresh and dried Sargassum sp. Pigment identiﬁ cation was conducted by Thin Layer Chromatography (TLC), Spectrophotometer and High Performance Liquid Chromatography (HPLC). The contents were analyzed by HPLC. Results showed that Sargassum sp. contain pigment fucoxanthin range from 21.80 to 73.10%, chlorophyll a range from 0.73 to 54.96%, chlorophyll c range from 0.28 to 1.09% and carotene 0.38%. The research results showed that fresh and dry Sargassum sp. contain same pigment composition that were as carotene, pheophytin a, chlorophyll a, chlorophyll c and fucoxanthin.